Voice of America News as Voluminous Reading Material for Mid-frequency Vocabulary Learning. (December 2019) - Hsu, Wenhua
Schmitt and Schmitt (2014) labelled the first 4, 000 to 9, 000 word families as mid-frequency vocabulary and highlighted its essential nature based on Nation's (2006) estimate that knowledge of the first 9, 000 word families would provide 98% coverage of various texts. To attain this goal, this study first measured the vocabulary level of Voice of America (VOA) news for its potential as voluminous reading material for mid-frequency vocabulary learning. Then it investigated how much VOA news input is needed to encounter most of the first 9, 000 word families enough times for learning to occur. To get different sized corpora, every 500, 000 words of VOA news were incrementally added to examine mid-frequency words. Results show that VOA news reached the sixth 1, 000-word-family level at 98% text coverage. Corpus sizes of 0.5 to 6 million words provided an average of 12+ repetitions for most of the words from the fourth to ninth 1, 000-word-family levels. The figures may serve as a reference for English extensive reading practitioners and learners who are concerned with mid-frequency vocabulary learning.